2011
DOI: 10.1111/j.1365-294x.2011.05391.x
|View full text |Cite
|
Sign up to set email alerts
|

Social organization and genetic structure: insights from codistributed bat populations

Abstract: The impact of ecology and social organization on genetic structure at landscape spatial scales, where gene dynamics shape evolution as well as determine susceptibility to habitat fragmentation, is poorly understood. Attempts to assess these effects must take into account the potentially confounding effects of history. We used microsatellites to compare genetic structure in seven bat species with contrasting patterns of roosting ecology and social organization, all of which are codistributed in an ancient fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 78 publications
1
31
0
2
Order By: Relevance
“…Roosting ecology and social organization may generally be important predictors of genetic structuring in insectivorous Old World bats. Rossiter et al (2012) found that less vagile, treeroosting species exhibit reduced gene flow, even across continuous intact rain forest, compared to more wide-ranging colonial cave-roosting species, indicating that the former should be disproportionately affected by landscape-scale habitat fragmentation.…”
Section: Genetic Consequencesmentioning
confidence: 95%
“…Roosting ecology and social organization may generally be important predictors of genetic structuring in insectivorous Old World bats. Rossiter et al (2012) found that less vagile, treeroosting species exhibit reduced gene flow, even across continuous intact rain forest, compared to more wide-ranging colonial cave-roosting species, indicating that the former should be disproportionately affected by landscape-scale habitat fragmentation.…”
Section: Genetic Consequencesmentioning
confidence: 95%
“…Studies have documented that a "private bandwidth of frequency" may have crucial functions in social communication and sexual behavior, for example, allowing bats to recognize relative individuals or attract copulation partners of right species [34]. In mating season, the male greater horseshoe bats have a polygynous mating system and male territoriality [35]. Thus the malefemale reunion would be necessary for the successful copulation.…”
Section: Discussionmentioning
confidence: 99%
“…Artibeus jamaicensis se adapta fácilmente a diferentes tipos de hábitat, posee una alta movilidad y alta abundancia, lo cual le facilita un flujo génico alto entre sus poblaciones (Rossiter et al 2012;Vázquez-Domínguez et al 2013). Estos aspectos de la historia natural de A. jamaicensis dan lugar a los altos niveles de diversidad genética, y la baja diferenciación genética encontrados en las poblaciones de Pantaleón y Manacal.…”
Section: Discussionunclassified
“…La aclimatación a distintos tipos de hábitats (Clutton-Broock 1988), y la alta vagilidad de A. jamaicensis, le facilita un flujo génico alto entre sus poblaciones, lo que reduce su diferenciación genética (Carstens et al 2004;Rossiter et al 2012;Vázquez-Domínguez et al 2013;Del Real-Monroy et al 2014). La conexión entre las poblaciones de A. jamaicensis es sostenida por el resultado del AMOVA, el cual indica que el mayor porcentaje de variación genética se reparte entre los individuos dentro de las poblaciones (94.62%).…”
Section: Discussionunclassified